Enmiendas edáficas: efectos en la biota del suelo y comportamiento agronómico del cultivo de banano - Campoverde Ramirez, Emerson Adalberto (Machala : Universidad Técnica de Machala, 2022)
The physicochemical characteristics of the soil have been affected by the excessive application of agrochemicals, which have reduced the beneficial microbial population causing problems such as: loss of fertility, compaction, acid pH, increase in phytopathogens, reducing crop productivity. The objective was to evaluate the effects of the application of three edaphic amendments on the microbiota, % of M.O., C.E., pH of the soil and its effects on the agronomic behavior of the banana crop. The treatments were: T1 (10 g Biochar + 40 g of NPK physical mixture + 500 mL of ME), T2 (100 g Compost + 40 g of NPK + 500 mL of ME), T3 (100 g Zeolite + 40 g of NPK + 500 mL of ME) and T4 (Control farm 40 g NPK + 40 g of TerraSoil). The results show that T1 forms an ideal habitat for the development of beneficial microorganisms such as Trichoderma spp., Bacillus spp., Beauveria bassiana compared to T4 where only phytopathogenic microorganisms such as Fusarium spp, Cladosporium spp., Penicillium spp. and Rhizopus spp. The application of biochar improves the agronomic behavior, accelerates the cutting time, increases the height of the return, the weight of the bunch and improves the conversion. The results of T2 and T3 are similar to each other in terms of agronomic parameters and health.
Las características fisicoquímicas del suelo se han visto afectadas por la excesiva aplicación de agroquímicos, que han reducido la población microbiana benéfica causando problemas como: pérdida de fertilidad, compactación, pH ácido, incremento de fitopatógenos, reduciendo la productividad del cultivo. El objetivo fue evaluar los efectos de la aplicación de tres enmiendas edáficas en la microbiota, % de M.O., C.E., pH del suelo y sus efectos en el comportamiento agronómico del cultivo de banano. Los tratamientos fueron: T1 (10 g Biochar + 40 g de NPK mezcla física + 500 mL de ME), T2 (100 g Compost + 40 g de NPK + 500 mL de ME), T3 (100 g Zeolita + 40 g de NPK + 500 mL de ME) y T4 (Testigo hacienda 40 g NPK + 40 g de TerraSoil). Los resultados demuestran que el T1 forma un hábitat ideal para el desarrollo de microorganismos benéficos como Trichoderma spp., Bacillus spp., Beauveria bassiana en comparación al T4 donde solo se hallan microorganismos fitopatógenos como Fusarium spp, Cladosporium spp., Penicillium spp. y Rhizopus spp. La aplicación de biochar mejora el comportamiento agronómico, acelera el tiempo de corte, incrementa la altura del retorno, el peso del racimo y mejora la conversión. Los resultados del T2 y T3 son similares entre sí en cuanto a parámetros agronómicos y sanidad.
Keywords: MICROORGANISMOS EFICIENTES; PHYTOPATHOGENS; BIOCHAR; BIOCHAR; ZEOLITA; COMPOST